Another Week, Another Scandal: Immigration Dilemmas - Reisberg, Liz; Altbach, Philip (International Higher Education, 2013)
Immigration regulations for international students seem to be changing somewhat unpredictably of late, in major receiving countries. In several English-speaking nations, immigration regulation has become a significant policy issue, and international students are the frequent focus of recent crackdowns. These changes have the potential for altering the landscape of global student flows and might even slow the increases in student numbers of the past two decades. In this context, the expansion of recent years might actually have been a temporary “bubble."